INTEGRAL ESTIMATION OF OXIDATIVE STATUS IN PATIENTS WITH ACUTE TOXIC HEPATITIS AND CHRONIC ALCOHOLIC LIVER DISEASE - A. Y. Shchupak; O. A. Lebedko; V. V. Yukhno (Неотложная медицинская помощь, 2016)
BACKGROUND Acute toxic hepatitis associated with acute poisoning with alcohol-containing disinfectants remains a medical and social problem.MATERIAL AND METHODS With an aid of chemiluminescence, we performed the integrated assessment of the oxidative status in the blood serum and homogenized liver biopsy tissue of 62 patients with the diagnosis «severe acute toxic hepatitis associated with the use of alcohol-containing disinfectants».RESULTS The research showed that at the onset of a disease, patients with acute toxic hepatitis had an expressed activation of free radical oxidation of the blood serum and biopsy tissue. This was indicated by almost double increase in the intensity of free radicals generation (Ssp). This signifi cantly increased production of peroxide (Sind-1) and hydroxyl radicals (Slum) — 2.5 and 1.86 times, respectively; also, it increased concentration of lipid hydroperoxides (h) almost three times, evidencing activation of the initial stage of lipid peroxidation There was no statistically signifi cant fall of figures indicating the liver parenchymal oxidative status 30 days after the admission. The same situation was observed 6 months after the beginning of the study.CONCLUSION Analyzing chemiluminescence scans of blood serums up to 30 days from admission, it is possible to conclude indirectly on a condition of the oxidative status in a liver parenchyma of patients.